VD_FINDINFO HC / 2016 / 400 vom 26. April 2016 - VD Tribunal cantonal (2016)
PROCÈS DEVENU SANS OBJET, MESURE DE CONTRAINTEDROIT DES ÉTRANGERS, DÉTENTION AUX FINS D'EXPULSION | 30 LVLEtr, 31 LVLEtr, 242 CPC (CH)